Complexin arrests a pool of docked vesicles for fast Ca2+ -dependent release - Malsam, Jörg; Parisotto, Daniel; Malsam, Andrea; Krause, Jean Michel; Söllner, Thomas (The EMBO journal, 2012)
Regulated exocytosis requires that the assembly of the basic membrane fusion machinery is temporarily arrested. Synchronized membrane fusion is then caused by a specific trigger—a local rise of the Ca2+ concentration. Using reconstituted giant unilamellar vesicles (GUVs), we have analysed the role of complexin and membrane‐anchored synaptotagmin 1 in arresting and synchronizing fusion by lipid‐mixing and cryo‐electron microscopy. We find that they mediate the formation and consumption of docked small unilamellar vesicles (SUVs) via the following sequence of events: Synaptotagmin 1 mediates v‐SNARE‐SUV docking to t‐SNARE‐GUVs in a Ca2+‐independent manner. Complexin blocks vesicle consumption, causing accumulation of docked vesicles. Together with synaptotagmin 1, complexin synchronizes and stimulates rapid fusion of accumulated docked vesicles in response to physiological Ca2+ concentrations. Thus, the reconstituted assay resolves both the stimulatory and inhibitory function of complexin and mimics key aspects of synaptic vesicle fusion.
Die Zahl 2 und das Zeichen + sind im Text hochgestellt
Gesehen am 11.10.2018